The impact of the first year of the Coronavirus (COVID- 19) pandemic on antiquities looting and illicit trafficking in archaeological materials: Palestine as a case study - Al-Houdalieh, Salah Hussein (Journal of Humanities & Social Sciences, 2022)
This present study focuses on the impact of the COVID- 19 pandemic, in its first year of outbreak (5/3/2020 – 5/3/2021), on the archaeological and historical sites and features throughout the West Bank. This study aims to identify the extent and scale of the encroachments on these sites and features, including antiquities looting, destruction, and illicit trade in cultural material. The methodology implemented in this study consisted of a review of the existing scholarly literature related to this subject, studying and analyzing the database archive of the Tourism and Antiquities Police Directorate, on- site observations during field visits to archaeological sites, and on first- hand information provided by interviewees.This study pointed the author to several main findings and conclusions, including: (a) that the COVID- 19 pandemic did not negatively affect the phenomenon of the antiquities looting and trafficking in material culture compared to the previous year; (b) the closures and restrictions imposed by the Palestinian authorities on the movement of the West Bank population created an ideal environment for antiquities looters to dig, with reduced risk of detection; (c) first- hand information provided by interviewees indicates that the database of the Tourism and Antiquities Police Directorate's archive does not reflect the realities of what is actually happening on the ground; and finally, (d) that the majority of the confiscated archaeological materials, according to some of the interviewees, involved the amateur middlemen's use of social media to sell their looted objects.
Keywords: COVID- 19 pandemic; the epidemics throughout history; antiquities looting; trafficking in antiquities; Palestine